the Impact of Corporate Governance Mechanism on Firm Performance: Empirical Evidence in China - Wang, Weizheng (2019)
The purpose of this study is to test the impact of corporate governance determinants on firm performance. In this research, panel data that consists of 98 China listed companies under SSE 180 Index during a 5-year period from 2014 to 2018 is utilized. In the sample of selected companies, statistical results show a statically significant and economically important relationship between governance determinants and firm performance which is measured by Tobin’s Q and return on assets respectively. The governance determinants that I examine in this study include board size, board independence, CEO duality, ownership concentration, audit committee independence and executive remuneration. The findings reveal that selected determinants are associated with performance significantly.